Extraction of lignosulfonate using supported liquid membrane process - Chen, Ke Xian, 1990-, author; Norasikin Othman, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper Sarjana Muda Kejuruteraan (Kimia) - Universiti Teknologi Malaysia, 2013